Antipsychotics and neutropoenia: An update - Luis Menéndez Rodríguez; Jose Angel Méndez Sánchez; Martin Menéndez Rodríguez; Antonio Iglesias Pérez; Santiago Fernández Blas; Maria Del Carmen Hernández Sánchez (Annals of Psychiatry and Treatment - Peertechz Publications, 2021)
Background and objectives: Drugs are a common reason for neutropoenia. The aim of this paper is to review the scientific evidence available in regard to cases of neutropoenia associated with the use of antipsychotics. Methods: A bibliographic review of the last five years collected in Pubmed, Uptodate, specifications of antipsychotics and the most important Clinical Practice Guidelines, was performed. Results: The frequency of neutropoenia associated with the use of antipsychotics and agranulocytosis is 3% and 1%, respectively. Neutropoenia is most common during the first three months of treatment. Some risk factors are prior neutropoenia, age, sex, comorbidities or genetic susceptibility. Mortality is extremely rare. Most cases of neutropoenia patients are free of symptoms and they are detected in the laboratory. However, when neutropoenia is severe, the patient can even begin to present sepsis. It is recommended undertaking healthcare education for carers and patients on alarm data. The use of clozapine has a protocol for specific management and monitoring, which reduced the incidence of agranulocytosis and mortality. The incidence of neutropoenia is lower with second and third generation antipsychotics compared to clozapine. Conclusion: The incidence of neutropoenia with antipsychotics is low. However, it is a potentially severe adverse effect. Blood work up in series needs to be performed during treatment with antipsychotics. It is possible that drugs with major antipsychotic potential such as clozapine are under used because of difficulties with their management and monitoring.